A novel fluorescence immunoassay for the quantitative detection of HPV16 L1 antibodies in human serum samples using ZnCdSe/ZnS quantum dot-labeled antibodies - Aiping Wang; Cheng Xin; Zhuting Chen; Jingming Zhou; Yumei Chen; Yankai Liu; Hongliang Liu; Chao Liang; Xifang Zhu; Yanhua Qi; Gaiping Zhang (Microbiology Spectrum)
ABSTRACT Human papillomavirus type 16 (HPV16) is a high-risk virus linked to cervical cancer, primarily through its oncogenic proteins E6 and E7. The HPV16-L1 protein, the major capsid component, plays a key role in capsid formation and immune response. Monitoring anti-HPV16-L1 antibodies in serum is crucial for understanding infection dynamics and vaccine efficacy. This study aimed to develop a novel quantum dot-labeled blocking enzyme-linked immunosorbent assay (QDs-B-ELISA) for the quantitative detection of anti-HPV16-L1 antibodies. Monoclonal antibodies were produced and characterized against HPV16-L1 virus-like particles. A QDs-B-ELISA method was developed based on these antibodies and evaluated using 199 serum samples with previously established HPV16 status (“known” samples) and 170 serum samples with unknown HPV16 status at the time of testing (“unknown” samples). The diagnostic accuracy, sensitivity, specificity, and quantitative detection range of the QDs-B-ELISA were assessed and compared with commercial ELISA kits. The established QDs-B-ELISA exhibited high diagnostic accuracy (area under the curve, AUC = 0.9945), sensitivity (95.83%), and specificity (96.85%) for known serum samples. The lower limit of HPV16 antibody concentration detected by QDs-B-ELISA (0.0875 IU/mL) was considerably lower than that of the commercial ELISA kit, the Human Anti-HPV16-L1 Antibody (IgG) ELISA Kit (LS-F10262-1, Lsbio) (0.35 IU/mL), with a quantitative detection range of 13–1,737.8 IU/mL. When analyzing unknown human serum samples, the QDs-B-ELISA demonstrated a 97.06% agreement with commercial kits, and both inter-assay and intra-assay coefficients of variation were below 10%. The QDs-B-ELISA demonstrated high stability, sensitivity, and specificity, offering a valuable tool for surveillance and epidemiological studies of HPV16 infection.IMPORTANCEThis study introduces a novel quantum dot-labeled blocking enzyme-linked immunosorbent assay for detecting anti-HPV16-L1 antibodies, offering superior sensitivity and specificity compared to conventional methods. The improved performance enables more accurate HPV16 surveillance, epidemiological studies, and vaccine efficacy monitoring. This advancement may enhance early detection and risk assessment of HPV16 infections.